DECISION TREE PADA PENILAIAN PERFORMA LAYANAN DRIVER GOJEK DENGAN ALGORITMA C4.5 - Uape, Frederikus Cyriaco Leu Le; Elisa, Erlin (LPPM Universitas Putera Batam, 2023)
Transportation is an important means to support daily activities and operations, be it private transportation or public transportation. This study will analyze the level of customer satisfaction as a public vehicle user, in this case the author utilizes data on customers who use and utilize the gojek application as a means of transportation, using a questionnaire data collection technique, the writer will determine client satisfaction levels using the variables Tangible, Reliability, Responsiveness, Assurance, Empathy. The analytical Data mining with the is a technique employed in this investigation. concept of the Algorithm C4.5 classification which can show the results of the highest Entrophy and gain values modeled as a decision tree with the aim that the results obtained can be a guide for gojek partners to service and increase customers. Considering the outcomes of the classicization It is demonstrated by the C4.5 algorithm that the accuracy achieves 75.33% where the factors that become the assessment of satisfaction are Tangible, Reliability.